Analysis of high-flux solar irradiation distribution characteristic for solar thermochemical energy storage application. (25th November 2020) - Jiang, Boshu; Guene Lougou, Bachirou; Zhang, Hao; Wang, Wei; Han, Dongmei; Shuai, Yong
Abstract: Designing equipment that meets the needs of efficient solar energy conversion and utilization is of great significance. In this paper, the design method of a solar simulator with Fresnel lens is studied from the perspective of concentrating solar energy research, high-temperature material testing, and optimal design method of reactor receiving surface. The Monte Carlo ray-tracing technique is applied to analyze the concentrating performance of a single xenon lamp-lens unit and hexagonal arrays of seven xenon lamp-lens units. For the single-disc concentrating unit, the Fresnel lens is analyzed and optimized for the reduction of the irradiance unevenness of the central spot, improvement in the peak irradiance, and the light convergence into different shapes to meet various needs. The numerical calculations are performed on the multi-disc simulator to obtain suitable installation conditions and reactor temperature distribution. A 42 kWel seven-disc Fresnel lens-based high-flux solar simulator is simulated. The solar simulator can provide a peak energy flow of 2.32 MW/m 2 with a spot diameter of 46 mm. The temperature of the cavity receiver reached 964 K and 1024 K when using a parabolic mirror and ellipsoidal mirror, respectively under the illumination of 6 kW xenon lamp. The concentrating unit coupled with the solar reactor exhibited reasonable thermal energy storage efficiency, as well as electro-thermal efficiency. The designed concentrating system could be considered suitable for high-temperature solar thermal and thermochemical applications, especially where there is a strict requirement for the shape or uniformity of the spot.